2019
DOI: 10.1002/14651858.cd012487.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Workplace interventions for increasing standing or walking for decreasing musculoskeletal symptoms in sedentary workers

Abstract: Analysis 2.4. Comparison 2 Treadmill workstation versus no intervention, Outcome 4 Proportion of participants with shoulder pain/discomfort follow-up short-term..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 164 publications
0
32
0
1
Order By: Relevance
“…Neck pain, shoulder stiffness, lower back pain, and mental health issues have also been noted as common reasons for decreased work performance. However, research on improving musculoskeletal symptoms due to oversitting lacks consistency in evidence due to the different intervention methods and periods that have been used and studied [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain, shoulder stiffness, lower back pain, and mental health issues have also been noted as common reasons for decreased work performance. However, research on improving musculoskeletal symptoms due to oversitting lacks consistency in evidence due to the different intervention methods and periods that have been used and studied [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plethora of health and performance issues associated with office work are likely to continue and expand in future work and workplaces [ 21 , 26 ]; thus, it is ever important to identify solutions to the challenges of mitigating risk and improving well-being within office work [ 27 ]. Environmental modifications such as sit-stand desks have been found to reduce sedentary work behavior in the short term, but no studies examining these modifications have demonstrated long-term effectiveness of reducing sedentary behavior [ 28 ] nor any effects in reducing pain-related disability in office workers [ 29 ]. Workplace wellness programs have also been developed to address health and performance issues; however, retention of positive change is difficult, and predictors of successful intervention are not yet well-understood [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Time spent in daily physical behaviors such as sitting, standing, and physical activity has profound physiological and psychological effects that may extend to the onset and progression of MSP [ 10 , 11 , 12 ] and the ability to remain at work [ 13 , 14 , 15 , 16 ]. Overall, very few studies have addressed physical behaviors at work in relation to sick leave specifically due to MSP [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sick leave due to MSP is of multifactorial origin and a variety of possible occupational determinants of future sick leave due to MSP have been identified-for example, high physical work demands and poor psychosocial working conditions [4][5][6][7][8][9]. Time spent in daily physical behaviors such as sitting, standing, and physical activity has profound physiological and psychological effects that may extend to the onset and progression of MSP [10][11][12] and the ability to remain at work [13][14][15][16]. Overall, very few studies have addressed physical behaviors at work in relation to sick leave specifically due to MSP [17].…”
Section: Introductionmentioning
confidence: 99%